EVALUATION OF THE PRINCIPAL’S ACADEMIC SUPERVISION PROGRAM ON TEACHER PERFORMANCE IN KINDERGARTEN AL-IKHLAS - Sadremi SADREMI; Ihsana El KHULUQO; Istaryatiningtias ISTARYATININGTIAS (Journal of Education and Leadership in Education, 2021)
This evaluation aims to assess the context, input, process and product of the implementation of academic supervision carried out by the head of Al-Ikhlas Kindergarten, Tangerang City. By using the CIPP (Context, Input, Process, Product) evaluation. The research results are expected to provide input to decision makers for the next program. Using a qualitative descriptive method with six teachers, one staff, and the principal of the school. The instruments used to collect data were triangulation, namely interviews, observation, and documentation study. Data validation, data analysis, data retrieval and verification. The findings of the context indicate the need for academic supervision based on the need to improve teacher performance. Evaluation of the process found that young teachers are smarter in their comprehension in providing learning. Positive impact product evaluation finds further action. The results of the evaluation can be concluded as follows (1) the principal in carrying out the design of the academic supervision program based on the objectives and principles of supervision. (2) The principal has implemented the supervision program according to predetermined procedures. (3) The results of supervision are not significant because the principal has not provided good feedback in improving teacher performance. (4) Coaching and training provided by school principals are not yet fully distributed to teachers. Therefore, the results of the supervision program did not provide significant results seen from the data on teachers whose qualifications had not been fulfilled.